Assessing midwives' breastfeeding knowledge: Properties of the Newborn Feeding Ability questionnaire and Breastfeeding Initiation Practices scale - Cantrill Ruth M; Creedy Debra K; Cooke Marie (BMC, 2008)
Abstract Background There are few reliable and valid tools to assess lactation and infant feeding knowledge and practices. This study tested the psychometric properties of two new scales, the Newborn Feeding Ability (NFA) questionnaire and Breastfeeding Initiation Practices (BIP) scale to assess midwives' breastfeeding knowledge and practices specific to breastfeeding initiation. Methods A national postal survey of Australian midwives (n = 3500) was conducted in October 2001. Reliability was determined through Cronbach's alpha coefficient and stability determined by a test-retest. Content validity was established through a critical review of literature and review by an expert panel. Construct validity was informed by an exploratory factor analysis and principle component analysis with varimax rotation. Correlations between NFA and BKQ knowledge subscale scores and BIP and BKQ practice subscale scores assessed criterion validity. A multiple hierarchical regression analysis determined predictive validity of the NFA and BIP. Results A response rate of 31.6% (n = 1107) was achieved. Adequate internal consistency was established for both instruments. Five factors on the NFA questionnaire were congruent with knowledge about effects of skin-to-skin contact, physiological stability, newborn innate abilities, work practices and effective breastfeeding. The BIP revealed three factors related to observing pre-feeding behavior, mother/baby care and attachment and positioning practices. Predictive validity of knowledge was moderate (r = 0.481, p < 0.01) and contributed to 31.5% of variance in reported practice. Midwives with high knowledge scores were more likely to report best practice when assisting mothers to initiate breastfeeding. Midwives with more personal breastfeeding experience scored higher on all scales. Conclusion The Newborn Feeding Ability questionnaire and the Breastfeeding Initiation Practices scale can contribute to practice development by assessing lactation and infant feeding knowledge and practice deficits. Individual learning needs can be identified, and effectiveness of education interventions evaluated using these tools. Further testing is required with other samples of midwives and health professionals involved in the promotion of breastfeeding.